TINJAUAN YURIDIS TERHADAP PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN MAKANAN TANPA TANGGAL KADALUARSA BERDASARKAN UUPK - Larasati Azahra; Johannes Sahat Tua Siadari, Haidy Alaina Shalatin, Zulfenia Arzilla Ramadhini, Muhammad Zeta Rifqi, (JOURNAL OF LAW AND NATION, 2023)
Packaged food is a very popular product in today's consumer market. However, the most important thing is to pay attention to the presence of packaged food without a clear expiration date. This raises concerns about the safety and quality of products used by consumers. The purpose of this study is to analyze consumer protection for packaged food using search terms as a reference. First, this research examines existing definitions and regulations for packaged food that does not have an expiration date. We then looked at the problems that can arise from packaged foods that do not have a clear expiration date. In addition, this study discusses various strategies that can be implemented by the government, producers and consumers to protect consumers from food packaging that does not have an expiration date. This strategy includes more regulation, tighter controls, better consumer awareness and product quality. The research method used is a normative legal approach, because it studies the provisions of laws and regulations, especially UUPK and other regulations related to them. We hope that the results of our group's research can contribute to a better understanding of consumer protection for food packaging with no expiration date. It is also expected to be able to provide effective policy recommendations to overcome this problem and increase consumer safety and confidence in the packaged food they consume.